ANALISIS SISTEM PENGUKURAN KINERJA PERBANKAN SYARIAH - Maya Indriastuti; Luluk M. Ifada (Conference In Business, Accounting, And Management (CBAM), 2015)
The existence of the banking sector as a sub-system in the economy of a country has an important role. Even in the modern life everyday, mostly involving nearly services from the banking sector. Through banks may be collected funds from the public in various forms of deposits. Related to that then  a banking company shall always improve its financial performance from year to year so that the confidence of society in  general  and  investors  in  particular  will  increase.  Therefore,  this  study  was conducted to analyze what measurement system in accordance with Islamic banking. This research using the company's Islamic banking in Indonesia is analyzed using multiple linear regression analysis using SPSS version 21. The analysis showed that the measurement system and performance assessment of Islamic banking can use a ANGELS (Amanah management, non-economic wealth, Give out, Earnings, capital and assets, Liquidity and sensitivity to market, and Socio-economic wealth), which is based on the principle of accountability inherent differences in the Islamic bank.  Keywords:  financial  performance,  Islamic  banking,  ANGELS,  the  principle  of accountability, and multiple linear regression.